Glioblastoma initiating cells are sensitive to histone demethylase inhibition due to epigenetic deregulation. Issue 5 (11th October 2019) - Mallm, Jan‐Philipp; Windisch, Paul; Biran, Alva; Gal, Zoltan; Schumacher, Sabrina; Glass, Rainer; Herold‐Mende, Christel; Meshorer, Eran; Barbus, Martje; Rippe, Karsten
Abstract : Tumor‐initiating cells are a subpopulation of cells that have self‐renewal capacity to regenerate a tumor. Here, we identify stem cell‐like chromatin features in human glioblastoma initiating cells (GICs) and link them to a loss of the repressive histone H3 lysine 9 trimethylation (H3K9me3) mark. Increasing H3K9me3 levels by histone demethylase inhibition led to cell death in GICs but not in their differentiated counterparts. The induction of apoptosis was accompanied by a loss of the activating H3 lysine 9 acetylation (H3K9ac) modification and accumulation of DNA damage and downregulation of DNA damage response genes. Upon knockdown of histone demethylases, KDM4C and KDM7A both differentiation and DNA damage were induced. Thus, the H3K9me3–H3K9ac equilibrium is crucial for GIC viability and represents a chromatin feature that can be exploited to specifically target this tumor subpopulation. Abstract : What's new? Glioblastoma‐initiating cells (GICs) exhibit stem cell‐like properties, including the capacity for continuous self‐renewal. In this study, owing to the relevance of histone methylation and acetylation to DNA repair and self‐renewal in mouse and human embryonic stem cells, the authors investigated chromatin features in GICs. Analyses show that GICs possess an open chromatin structure, with enrichment of histone acetylation and reduced methylation. Inhibition of the histone demethylases KDM4C and KDM7A, leading to global restoration of H3K9me3 levels, reduced viability and induced differentiation in GICs. The findings suggest that selective targeting of histone demethylases is a promising strategy for eliminating GIC subpopulations.